2013
DOI: 10.1007/978-3-642-38998-6_2
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Redirection on HTTP Adaptive Streaming Services in Federated CDNs

Abstract: Abstract. HTTP Adaptive Streaming (HAS) refers to a set of novel streaming services that allow clients to adapt video quality based on current network conditions. Their use of existing HTTP delivery infrastructure makes them perfectly suited for deployment on existing Content Delivery Networks (CDNs). Nevertheless, this leads to some new challenges, related to the distribution of content across servers and the latency caused by request redirection. The federation or interconnection of CDNs proliferates these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Our approach further increases the efficient use of the ISP's network by minimizing the negative impact of competing sessions on QoE. Famaey et al assess the impact of increased latency on QoE caused by the redirection of HAS requests in CDNs and propose updated request routing schemes in order to reduce the number of redirects [25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach further increases the efficient use of the ISP's network by minimizing the negative impact of competing sessions on QoE. Famaey et al assess the impact of increased latency on QoE caused by the redirection of HAS requests in CDNs and propose updated request routing schemes in order to reduce the number of redirects [25].…”
Section: Related Workmentioning
confidence: 99%
“…Since the decision variables a c,q are modeled as binary values, multiplying this decision variable with the corresponding µ c,q and σ c,q values allows a linear objective function. To this end, a history H c of previous quality decisions is required for every client c ∈ C. This history allows calculating the average quality µ c,q for every client c ∈ C and every possible quality decision q ∈ Q v for the next timeslot in Equation (25). The variation in quality σ c,q can be calculated for each client using the set of averages µ c,q for each quality decision q ∈ Q v as shown in Equation (26).…”
Section: Qoe-driven Quality Optimizationmentioning
confidence: 99%
“…The service providers that deliver content adaptation on a wide range of devices and networks, allow learners to receive improved user experience, with minimized storage and maintenance requirements on the server side. [8]. Their research has showed that the increased segment duration can have negative effects of on video quality when using the UpstreamRR policy [8].…”
Section: Related Workmentioning
confidence: 99%
“…[8]. Their research has showed that the increased segment duration can have negative effects of on video quality when using the UpstreamRR policy [8]. It also leads to increased start-up delay, slower convergence to the optimal quality and most importantly a significant increase in lag of streaming sessions compared to the live time [8].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation